Qualidade de vida relacionada à saúde de mães de crianças e adolescentes com paralisia cerebral - Guimarães, Ludmilla Rabelo (2012)
The cerebral palsy (CP) characterizes a heterogeneous group of posture and movement conditions, of non-progressive nature, which occurs in the developing brain and causes motor limitations in several degrees. The disability caused by the disease generates repercussions in the life and well-being of subjects and their families. Mothers, who often are the main caregivers, may present negative impact on their health and quality of life, but it isn t possible yet to state if the clinical and demographic factors are determinant to this injury. This study has, as its objectives, evaluating the health related quality of life (HRQOL) of mothers of children and adolescents with cerebral palsy (CP) in comparison with mothers of healthy children; verify the association between clinical/demographic variables and the HRQOL of mothers; evaluate the association between the HRQOL of the mothers compared with the HRQOL of their children. In this transversal study, it was accounted the participation of 100 mothers of children and adolescents with CP and 100 mothers of healthy children and adolescents. Every mother answered the generic questionnaire of HRQOL SF-36 by interview and Beck s Depression Inventory (BDI) through self-application. Both CHQ-PF50 and CHAQ were answered through self-application method by the mothers of patients with ages between 5 and 20 years and utilized for the correlation between the HRQOL of the patients and their mothers. Mothers of the PC group presented lower scores than the healthy group in every domain of the SF-36 (p≤0.05). Some associations were found between the SF-36 and the clinical/demographic variables: BDI presented a negative correlation (r= -0,21 a r= -0,60) with the domains of the SF-36; mother s age, patient s age, mother s scholarity were correlated with the mental component of the SF-36 (p≤0.05); unemployed mothers had lower scores in 3 domains of the SF-36 (p≤0.05); mothers of children in medication use had lower scores in the physical component with small effect size (p≤0.05). The motor gravity type of CP and scores in CHAQ had no correlation with the SF-36 (p≤0.05). Some correlations occurred between the physical and mental summaries (p≤0.05). Mothers of children and adolescents with CP presented negative mental and physical impact in their HRQOL in comparison with mothers of healthy children and adolescents. The greater the intensity of depressive symptoms was, the greater the injury in the HRQOL of the mothers. The mother s age, patient s age, mother s scholarity, employment situation and some dimensions of the HRQOL of their children presented association with the HRQOL of the mothers.